Association of Total Bilirubin With All-Cause and Cardiovascular Mortality in the General Population - Chen, Ziwei; He, Jing; Chen, Chu; Lu, Qi (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objective：The study aims to investigate the association of total bilirubin with all-cause and causes-specific mortality in the general population. Methods: A total of 37,234 adults from the United States National Health and Nutrition Examination Survey 1999-2014 were enrolled. Baseline levels of total bilirubin associated with risk of mortality were evaluated on a continuous scale (restricted cubic splines) and by quartile categories with Cox regression models. Results: Higher levels of total bilirubin was positively associated with an increased risk of all-cause mortality (hazard ratio [HR]1.59, 95% confidence interval [CI] 1.46-1.72; p<0.001). Compared with individuals with the lowest quartile of bilirubin, the multivariable adjusted hazard ratio for all-cause mortality was 1.25 (1.14-1.37) for individuals in the highest quartile. Restricted cubic splines indicated that the association was non-linear in cardiovascular mortality and cancer mortality while linear in all-cause mortality. Conclusions: Total bilirubin was associated with all-cause and cause-specific mortality in general population.